The New Approach to Estimation of the Hazard Function in Business Demography on Example of Data from New Zealand - Zajac, Pawel (Managerial Economics, 2013)
The author presents the new methodology for the estimation of the hazard function for the new born enterprise`s survival rate called FIRM. The methodology is based on construction of a stochastic process and is examined in the Monte Carlo simulation study with real data. The dataset is provided by Statistics New Zealand and contains all enterprises born in period between 2001–2010. Enterprises are divided in clusters according to the number of employees and for each cluster individual simulations are made. Achieved coefficients of determination in clusters are around 90%. The author finds substantial differences in survival probability according to employee count size in the company. Simulations done in this study allow to estimate mean and standard deviation of life duration for enterprises and prediction of the hazard function for each cluster.